Capsule Size Alters the Timing of Metabolic Alkalosis Following Sodium Bicarbonate Supplementation - Middlebrook, India; Peacock, Joe; Tinnion, Daniel J.; Leach, Nicholas K.; Hilton, Nathan P.; Saunders, Bryan; Sparks, S. Andy; Mc Naughton, Lars R. (Frontiers in Nutrition, 2021)
INTRODUCTION: Sodium bicarbonate (NaHCO3) is a well-established nutritional ergogenic aid that is typically ingested as a beverage or consumed in gelatin capsules. Whilst capsules may delay NaHCO3 release and reduce gastrointestinal (GI) side-effects compared with a beverage, it is currently unclear whether capsule size may influence acid-base responses and GI symptoms following supplementation. AIM: To determine the effects of NaHCO3 supplementation administered in different sized capsules on acid-base responses, GI symptoms and palatability. METHODS: Ten healthy males (mean ± SD: age 20 ± 2 y; height 1.80 ± 0.09 m; weight 78.0 ± 11.9 kg) underwent three testing sessions whereby 0.3 g∙kg–1 body mass NaHCO3 was consumed in either small (size 3), medium (size 0) or large (size 000) capsules. Capillary blood samples were procured pre-ingestion and every 10 min post-ingestion for 180 min. Blood samples were analysed using a Radiometer (Radiometer ABL800, Denmark) to determine blood bicarbonate concentration ([HCO3–]) and potential hydrogen (pH). Gastrointestinal (GI) symptoms were measured using a questionnaire at the same timepoints, whereas palatability was recorded pre-consumption. RESULTS: Capsule size had a significant effect on lag time (the time [HCO3-] changed Tlag) and the timing of peak blood [HCO3–](Tmax). Bicarbonate Tlag was significantly higher in the large (28 ± 4 min) compared with the small (13 ± 2 min) sized capsules (P = 0.009). Similarly, Tmax was significantly lower in the small capsule (13 ± 2 min) compared with both the medium (22 ± 6 min; P = 0.005) and large (28 ± 4 min; P = 0.001) sized capsules. The GI symptom scores were similar for small (3 ± 3 AU,), medium (5 ± 3 AU) and large (3 ± 3 AU) sized capsules, with no significant difference between symptom scores (F = 1.3, P = 0.310). Similarly, capsule size had no effect on palatability (F = 0.8, P = 0.409), with similar scores between different capsule sizes. CONCLUSION: Small capsule sizes led to quicker Tlag and Tmax of blood [HCO3–] compared to medium and large capsules, suggesting that individuals could supplement NaHCO3 in smaller capsules if they aim to increase buffering capacity more quickly.